Monitoring Vegetation Hotspots in Raparin Administration, Kurdistan Region, Using Remote Sensing and NDVI Time Series Analysis - Nasir, L. Dr. Salam Mahmood Nasir; Mohammed, Dr. Mohammed Watman Mohammed; Mohammed, A. L. Hemin Hussein Mohammed (Sulaimani Journal for Humanities, 2025)
Vegetation hotspots within the Raparin Independent Administration (RIA) or (Raparin Area) in the Kurdistan Region of Iraq are increasingly impacted by human activities, land use changes, and climate variability. Effective conservation and sustainable management of these ecologically sensitive areas require continuous monitoring of vegetation dynamics. This study analyzes vegetation cover changes in the Raparin region, northeastern Sulaimani Province, over 35 years (1990–2025) using multitemporal Normalized Difference Vegetation Index (NDVI) data derived from Landsat satellite imagery. The region’s complex topography, ranging from 500 to over 3,000 meters in elevation, and its semi-arid to cold continental climate provide a diverse ecological context for analysis. Results reveal a general decline in vegetation during the 1990s, followed by a gradual recovery in subsequent decades, with forested mountainous areas maintaining relative stability and functioning as biodiversity refuges. In contrast, lowland plains exhibit greater vegetation variability, influenced by agricultural practices, urbanization, and climatic fluctuations. Spatial hotspot analysis using the Getis-Ord Gi* statistic identifies a dense, stable belt of high vegetation productivity along the southern border with Iran, alongside fragmented low-productivity cold spots in plains and mountainous rocky zones. These findings emphasize the importance of targeted conservation efforts in forested hotspots and restoration initiatives in vulnerable areas. This study demonstrates the critical role of remote sensing and spatial analysis in monitoring vegetation dynamics and guiding biodiversity conservation under changing environmental and socio-economic conditions.
Keywords: Vegetation Hotspots; Remote Sensing; NDVI Time Series; Vegetation Dynamics; Raparin Independent Administration